Quercetin as a Protease (á-Chymotrypsin) Inhibitor - Bajracharya, GB; Thapa, DB (Nepal Journal of Science and Technology, 2014)
Quercetin, isolated from the skin of red onion bulb, was methylated to afford quercetin 3,3’,4’,7-tetramethyl ether in 83.3% yield. Quercetin has displayed α-chymotrypsin inhibitory effect (IC50 = 88.9 ± 2.5 ìg/ml), DPPH free radical scavenging activity (IC50 = 14.87 ìg/ml) and ferric reducing power (EC1 = 112.94 ìM/l equivalent to 1 mM/l FeSO4.7H2O), whereas no enhancement of these biological activities was observed using its tetramethyl ether derivative. DOI: http://dx.doi.org/10.3126/njst.v14i2.10420 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 91-96